MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI SDN 11 MANDAU MELALUI METODE DISCOVERY LEARNING - Zulrahmiati Yuda (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article discusses a study about students’ learning activities and learning outcomes through the Discovery Learning model. The implementation of the Discovery Learning model can improve individual discovery abilities and make the learning activity passive into active. The research was a Classroom Action Research (CAR) with a research design model of Kemmis and Mc. Taggart. The research was conducted at SDN 11 Mandau. The population involved 21 sixth-grade students, which consisted of 11 male and 10 female students. The research used quantitative descriptive analysis. Data collection techniques used observation, interviews, and evaluation tests at the end of the cycle. In the pre-cycle, the criteria for students’ learning activities were 38.09%. After implementing the Discovery Learning model, there was an improvement. In the first cycle, the criteria for students’ activities were 76.19%, and in the second cycle, students’ activity was 95.23% active to follow the learning process. Whilst, students’ learning outcomes in the pre-cycle were obtained at 42.85% with students’ completeness of 65.25. In Cycle I, it was obtained that students’ completeness was 71.42% with an average score of 75.50. In Cycle II, students’ learning completeness increased to 90.47% with an average of 84.25. On this occasion, the implementation of the Discovery Learning method in natural science learning subjects could increase students’ activities and learning outcomes in the teaching and learning process.